Analysis of Student Social Interaction in the Salted Egg Making Project in Elementary Schools - Anggraeni, Devia; Mustoip, Sofyan; Hanifah, Hanifah (EduBase : Journal of Basic Education, 2024)
This research aims to analyze students' social interactions in implementing the salted egg making project in elementary schools. With a qualitative approach, this research uses observation, interviews and documentation methods to collect data from fourth grade students involved in project activities. The focus of the research is how students communicate, work together, and resolve conflicts during activities. The research results show that the salted egg making project can improve students' social skills, including communication skills, joint decision making, and tolerance for differences of opinion. Students appear more active in sharing tasks and are responsible for their respective roles. In addition, it was found that teachers have an important role as facilitators to direct positive interactions between students. This activity also shows that project-based learning can be an effective means of developing students' social aspects in the school environment. Based on these findings, it is recommended that schools integrate similar activities in the curriculum to encourage the holistic development of students' social skills.